Agency and structure in the age of European disintegration - Orlando, Vittorio; Conrad, Maximilian (Frontiers in Political Science, 2024)
This article analyses the causal factors behind the Brexit vote, aiming to contribute to the literature on European disintegration. It addresses how, amidst external factors such as the EU debt crisis and the 2015 refugee crisis, pre-existing ideological forces deeply ingrained in a society can surface and steer a country's trajectory in relation to European integration. Employing a rigorous process-tracing design, it highlights the forces that led to the referendum and its outcome, identifying key patterns that can be extrapolated to comparable cases within the field of EU integration theory. The analysis operates at two levels: it scrutinizes the constraints faced by Cameron's government in the lead-up to the vote, and it probes the British electorate's attitude toward EU and how it was influenced by the Leave campaign. The study draws from an empirical case to identify some of the patterns of this ongoing political process.